Los recursos didácticos: elemento clave para mejorar la lecto escritura en el quinto grado de Educación General Básica - Jumbo Malla, Gelen Belen (2023)
The research about Didactic Resources: key element to improve reading and writing in the students of fifth grade of General Basic Education at "Cisol Educare", has as general objective: To determine the influence of the didactic resources in the improvement of reading and writing skills in the students of fifth grade of General Basic Education at "Cisol Educare" School, academic period 2022-2023. In the theoretical framework the topics related to the didactic resources and reading and writing skills were approached; the methods used were: scientific, descriptive, analytical, synthetic, inductive, deductive, statistical; in order to collect the literature information, the interview to the teacher was applied and the evaluation of reading and writing of Magallanes was applied to students, which allowed to know the errors that children made when they were reading and writing. The target population was twenty-six students and one teacher, in order to face the problem investigated, it was determined through the application of teaching resources in the different workshops and the test applied, that help to strengthen the reading and writing process, since, if they are applied correctly, it is possible to improve the learning of the students by maintaining the motivation and active participation of each one of them, however, the teacher does not implement this technique when teaching, so most students have problems in their academic performance. Finally, it was concluded that the didactic resources are very important in the classroom, because of they contribute to improve understanding, motivation, participation and attention of the students, achieving a good academic performance in each one of them, especially in the process of reading and writing. Key words: didactic resources, reading and writing, methods, techniques, learning, motivation, academic performance.